The Effect of Hot Water Scarification Duration on Germination and Growth of Indigofera zollingeriana Seeds - Tahing, Albertus; Semang, Agustinus; Vertygo, Stormy (Jurnal Biologi Tropis, 2024)
Indigofera zollingeriana is a type of leguminous plant that is excellent for cultivation as forage for ruminant livestock such as cattle, buffalo, goats, and sheep. This study aims to determine the effect of the duration of hot water scarification on the germination of Indigofera zollingeriana seeds. The research was conducted at the Livestock Feed Technology Laboratory of the State Agricultural Polytechnic of Kupang. The study was carried out for 2 weeks using a Completely Randomized Design with 4 treatments and 5 replications, namely P0: without hot water scarification, P1: hot water scarification at 65°C for 30 minutes, P2: hot water scarification at 65°C for 60 minutes, and P3: hot water scarification at 65°C for 90 minutes. The variables measured in this study were germination percentage, mean daily germination, and seedling height. The data obtained were analyzed using analysis of variance (ANOVA), and if there was a significant effect, it was followed by Duncan's test. The results showed that the effect of scarification of Indigofera zollingeriana seeds with hot water at 65°C for different durations significantly affected the parameters of germination percentage and mean daily germination, with the treatment without scarification providing the best results. This could be due to the prolonged duration of soaking, which caused the seeds to experience heat stress. As for the seedling height parameter, the treatment did not have a significant effect. Therefore, hot water scarification with excessively long durations is not recommended as a strategy to promote germination and growth of these seeds.